Using structural equation modeling to investigate change and response shift in patient-reported outcomes: practical considerations and recommendations - Verdam, M. G. E. (Qual Life Res, 2021)
BACKGROUND: Patient-reported outcomes (PROs) are of increasing importance for health-care evaluations. However, the interpretation of change in PROs may be obfuscated due to changes in the meaning of the self-evaluation, i.e., response shift. Structural equation modeling (SEM) is the most widely used statistical approach for the investigation of response shift. Yet, non-technical descriptions of SEM for response shift investigation are lacking. Moreover, application of SEM is not straightforward and requires sequential decision-making practices that have not received much attention in the literature. AIMS: To stimulate appropriate applications and interpretations of SEM for the investigation of response shift, the current paper aims to (1) provide an accessible description of the SEM operationalizations of change that are relevant for response shift investigation; (2) discuss practical considerations in applying SEM; and (3) provide guidelines and recommendations for researchers who want to use SEM for the investigation and interpretation of change and response shift in PROs. CONCLUSION: Appropriate applications and interpretations of SEM for the detection of response shift will help to improve our understanding of response shift phenomena and thus change in PROs. Better understanding of patients’ perceived health trajectories will ultimately help to adopt more effective treatments and thus enhance patients’ wellbeing. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11136-020-02742-9.